Comme une aiguille sur un sillon d’asphalte - Julien Glauser (Projets de Paysage)
Focusing on the bodily sensations induced by street skateboarding, this article focuses on knowledge of the environment shaped by the practice of a sport. These sensory and kinetic relationships that the skateboard "tool" renders possible lead to a different understanding of the city. The skateboard reveals such aspects as the quality of the ground surface as well as automobile and pedestrian congestion. From this detailed perception comes a precise knowledge of the built-up environment and the forms of governance of places both public and private open to the public. Through his work with skateboarders in Tokyo, the author shows how the search for spots - places that are good for skating - and the observation of security measures transform the skaters' perception of their environment. This particular understanding of the urban environment is reflected in the still and moving images produced by the skateboarding community, which in turn feed the imaginary experience shared by skateboarders through their individual practice of the sport.